Pengaruh Perkembangan Motor Custom Dan Aspek Legalitas Terhadap Minat Konsumen Pada Motor Modifikasi Di Kota Metro - Irawan, Yudi; Rahayu, Sri Retnaning; Riyanto, Kuncoro Budi (Universitas Muhammadiyah Metro, 2022)
The influence of the development of custom motorbikes is currently so rapid and spreading from young to old. The main problems with custom motorbikes include the safety and legality aspects of the custom motorbike. The purpose of this study to determine effect of the development of custom motorbikes and the legality on consumer interest in modified motorbikes. The research design is quantitative research or verification research. The method is documentation method. The object aredevelopment of custom motorbikes, legality and consumer interest. This research activity in modified motorcycle workshops in Metro City. The data collection technique used a questionnaire with a questionnaire. The analytical tool is descriptive analysis and multiple linear regression analysis with SPSS. Results showed that partially the development of custom motorbikes and legality had a significant effect on consumer interest. Simultaneously it also shows that the development of custom motorbikes and the legality of custom motorbikes on consumer interest.